Phase Behavior and Physical Properties of New Biobased Ionic Liquid Crystals - Toledo Hijo, A.A.C. (American Chemical Society, 2017)
Protic ionic liquids (PILs) have emerged as promising compounds and attracted the interest of the industry and the academy community, due to their easy preparation and unique properties. In the context of green chemistry, the use of biocompounds, such as fatty acids, for their synthesis could disclose a possible alternative way to produce ILs with a low or nontoxic effect and, consequently, expanding their applicability in biobased processes or in the development of bioproducts. This work addressed efforts to a better comprehension of the complex solid-liquid crystal-liquid thermodynamic equilibrium of 20 new PILs synthesized by using fatty acids commonly found in vegetable oils, as well as their rheological profile and self-assembling ability. The work revealed that their phase equilibrium and physical properties are significantly impacted by the structure of the ions used for their synthesis. The use of unsaturated fatty acids and bis(2-hydroxyethyl)ammonium for the synthesis of these biobased ILs led to a drastic decreasing of their melting temperatures. Also, the longest alkyl chain fatty acids promoted higher self-assembling and more stable mesophases. Besides their sustainable appeal, the marked high viscosity, non-Newtonian profile, and very low critical micellar concentration values of the PIL crystals here disclosed make them interesting renewable compounds with potential applications as emulsifiers, stabilizers, thickeners, or biolubricants. © 2017 American Chemical Society.